Spatial Estimation of PM2.5 Exposure and its Association with Asthma Exacerbation: A Prospective Study in Thai Children - Kornnasa Chankaew; Ratchaneewan Sinitkul; Wiparat Manuyakorn; Koonkoaw Roekworachai; Harutai Kamalaporn (Ubiquity Press, 2022)
Background: The acceptable fine particulate matter (PM2.5) level in Thailand is double the recommendation of the World Health Organization. It is necessary to have an accurate measure of PM2.5 exposure and its association with health problems in vulnerable groups such as asthma exacerbation in Thai children to urge the Clean Air Act in Thailand, which is currently in the process of revision. Objective: To study the association between PM2.5 exposure and asthma exacerbation in children living in Bangkok Metropolitan Region and Chiang Mai Province. Methods: A pilot prospective observational study was conducted at the Chest and Allergy clinic at Ramathibodi Hospital, Mahidol University, Bangkok and at the Chest Clinic at Nakornping Hospital, Chiang Mai, Thailand, from June 2020 to February 2021. Children with asthma, aged 5-18 years old, were recruited. Respiratory symptoms, including cough, chest tightness, dyspnea or wheezing, peak expiratory flow rate, and asthma exacerbation, were recorded twice daily by caregivers. Estimated average daily PM2.5 exposure levels were calculated using ArcGIS® at exacerbation day, three days before exacerbation (lag day 3), and 7 days before exacerbation (lag day 7). Regression analysis was applied to examine the association between PM2.5 exposure and asthma exacerbation. Findings: Seventy asthmatic patients were enrolled. The median age was 9.7 (IQR 5-18) years old. There were 53 respiratory symptoms, 5 admissions, and 1 intensive care unit admission. Daily PM2.5 levels above 12 mcg/m3 (the US cut-off level for the sensitive group) has higher sensitivity to detect asthma exacerbation compared to Thai cut-off level for the sensitive group (37 mcg/m3) (sensitivity 98.2% vs 32.1%). The average daily PM2.5 level exposure at lag day 3 in the exacerbation vs the non-exacerbation group was 27.5 and 13.6 mcg/m3 (p < 0.01), respectively. The daily PM2.5 level at lag day 3 was also correlated with an acute asthmatic attack (r = 0.62, p < 0.01) with the 0.2 events increasing of asthmatic exacerbation every 10 mcg/m3 of increment of daily PM2.5 level. Conclusions: Our findings suggest that asthmatic children are sensitive to daily PM2.5 levels above 12 mcg/m3. Exposure to high daily PM2.5 levels can lead to asthma exacerbation within three days. Further participant recruitment is needed to emphasize this association and establish the national data.